Léo Dex et les romans « aérostatiques » - Puyo, Jean-Yves (Studia Romanica Posnaniensia, 2023)
Between 1895 and 1904, Captain Edouard Deburaux, under the name Léo Dex, wrote several novels that fully embraced the codes of the geographical novel. Most of his writings, following in the footsteps of Jules Verne’s Cinq semaines en ballon (1863), were intended to take the reader mainly to Africa. So, is he a mere imitator? In fact, he differs from Verne in that he himself was a nationally and internationally recognized balloonist. And if he did not invent the “balloon novel”, he was nonetheless the most prolific contributor to the genre.